Transcriptome analysis revealed the role of mTOR and MAPK signaling pathways in the white strain of Hypsizygus marmoreus extracts-induced cell death of human hepatoma Hep3B cells - Lee, Kun-Tsung; Chen, Li-Yun; Li, Wei-Sung; Lee, Hong-Zin (Frontiers in Pharmacology, 2022)
The aim of this study was to investigate the anticancer mechanisms of white genius mushroom (WGM). WGM is a popular edible mushroom in Taiwan and has been demonstrated to mediate potent antiproliferation effects against human Hep3B liver cancer cells in our previous study. According to next generation sequencing technology and KEGG pathway enrichment analysis, mTOR and MAPK signaling pathways were markedly changed during treatment with WGM extracts in Hep3B cells. Therefore, this study examined the effects of WGM extracts on the expression of mTOR and MAPK signaling pathway-related proteins, such as PI3K, Akt, mTOR, Ras, Raf, MEK, ERK, p38 and JNK in Hep3B cells. According to the results of immunoblotting, we demonstrated that the protein expression of the members of PI3K/Akt/mTOR and MAPK signaling pathways were involved in WGM extracts-induced cell death. Furthermore, the inhibitors of PI3K/Akt/mTOR and MAPK signaling pathways such as rapamycin, MK2206, LY3214996 and SB202190, blocked the induction of cell death and vacuoles formation induced by WGM extracts. This study also demonstrated that WGM extracts is able to inhibit Hep3B cell migration and colony formation in a dose-dependent manner. In addition to being a very popular food, WGM should be a pharmacologically safe natural agent for cancer treatment. Therefore, WGM might be designed to develop into a dietary chemopreventive agent for the cancer treatment.